Implementation and Use of Green Manures for Weed Suppression in Sequential Maize Cropping - Amilcar Servín Niz; Modesto Osmar Da Silva Oviedo; Eulalio Morel López; Derlys López Ávalos; Hugo González Villalba; Alcides Fernández Sánchez; Pablo Fankhauser Solis; Willian Insfrán (International Journal of Agronomy)
The ground cover produced by green manures has a direct influence on weed suppression and, in addition, the biomass produced by these same plants influences crop growth. This study was carried out to compare the effect of green manure species on the incidence of weeds, in sequence, in order to evaluate the effects of the use of green manure cover on the productive characteristics of maize plants. A completely randomised experimental design was used, with 11 treatments and 4 replications. The treatments were cover crops Canavalia ensiformis (T1), Cajanus cajan (T2), Stizolobium pruriens (T3), Crotalaria juncea (T4), Phaseolus vulgaris (T5), Stizolobium trigre (T6), Stizolobium aterrimum (T7), Crotalaria retusa (T8), Crotalaria breviflora (T9), Dolichos lablab (T10), and conventional system (T11). Ninety days after sowing, the green manures were cut, and 30 days after the green manures were cut, the hybrid maize Crop Top 520 was sown. The variables evaluated in relation to the planting of green manures were the green and dry biomass of green manures, alongside the green biomass of weeds and suppression of weeds. Concerning maize plants, the variables evaluated were plant height at 60 DAS, stalk diameter at 60 DAS, number of grain rows per ear, number of grains per grain row, and yield. The averages were subsequently analyzed using Tukey’s test at 95% significance level. The use of green manure significantly reduces the green mass of weeds up to 90 days due to lack of access to light of the weeds, which reduces their appearance and growth. Stizolobium aterrimum showed the best results both as a dry mass producer and weed suppressor and also as a yield enhancer in maize crops.